2019
DOI: 10.1097/icl.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Efficacy of a Hydrogen Peroxide Lens Care Solution Incorporating a Novel Wetting Agent

Abstract: Both solutions eliminated or reduced populations of FDA/ISO compendial bacteria and fungi as well as clinically relevant microorganisms and Acanthamoeba trophozoites and cysts. The addition of EOBO-21 to the 3% H2O2 lens care solution had no impact on antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…To date, there are many studies on the antibiotic effect of hydrogen peroxide against microorganisms attached to SCLs. [1][2][3][4][5][6][7] For example, hydrogen peroxide was effective against clinical bacterial isolates and not affected by organic soils in tears. Retuerto and associates examined microbiome adherent to CLs and the association of bacterial communities with the use of lens care solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are many studies on the antibiotic effect of hydrogen peroxide against microorganisms attached to SCLs. [1][2][3][4][5][6][7] For example, hydrogen peroxide was effective against clinical bacterial isolates and not affected by organic soils in tears. Retuerto and associates examined microbiome adherent to CLs and the association of bacterial communities with the use of lens care solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide has been reported to be superior to MPS in disinfecting and cleaning effects. [1][2][3][4][5] It has also been reported that microorganisms such as bacteria, viruses, fungi, and Acanthamoeba attached to SCLs are killed by soaking with 3% hydrogen peroxide for 6 hours. 6 However, the cleaning effect of hydrogen peroxide on pollens attached to SCLs is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Gabriel et al 7,8 reported on the antimicrobial efficacy of CCP in the Stand-alone and Regimen tests. Solutions in CCP lens cases with neutralizing discs were inoculated with organisms and evaluated for microbial loads at DT.…”
Section: Antimicrobial Efficacymentioning
confidence: 99%
“…The antimicrobial efficacy of a disinfecting solution can be further challenged using clinically relevant ocular strains isolated from patients with adverse events (AEs), as these strains may be more resistant to disinfection than laboratory strains. Gabriel et al 7 tested CCP against two clinically relevant ocular isolates from infections of P. aeruginosa and one strain each of Stenotrophomonas maltophilia and S. aureus. CCP reduced all clinically relevant bacterial strains by >4.5 logs, therefore exceeding the ISO 3-log reduction requirement for bacteria ( Figure 2).…”
Section: Antimicrobial Efficacymentioning
confidence: 99%
See 1 more Smart Citation